2002
DOI: 10.1097/00005373-200206000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trauma Team Performance Using an Advanced Human Patient Simulator for Resuscitation Training

Abstract: No studies have validated the use of the HPS as an effective teaching or evaluation tool in the complex field of trauma resuscitation. These pilot data demonstrate the ability to evaluate trauma team performance in a reproducible fashion. In addition, we were able to document a significant improvement in team performance after a 28-day trauma refresher course, with scores approaching those of the expert teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(128 citation statements)
references
References 19 publications
1
125
0
2
Order By: Relevance
“…10 It is now widely used for teaching clinical expertise in domains that are infrequently encountered in the clinical setting [11][12][13] and has proven to be effective in promoting the acquisition of the knowledge, skills, and attitudes necessary to perform effectively as an emergency physician. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] SBE affords residents the opportunity to apply and improve their individual and team crisis resource management (CRM) skills, 27 as well as practice recognition and medical management of rare events. 28 The opportunity to practice in a safe learning environment with dedicated time for debriefing allows the development of competence that is not easily achieved in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is now widely used for teaching clinical expertise in domains that are infrequently encountered in the clinical setting [11][12][13] and has proven to be effective in promoting the acquisition of the knowledge, skills, and attitudes necessary to perform effectively as an emergency physician. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] SBE affords residents the opportunity to apply and improve their individual and team crisis resource management (CRM) skills, 27 as well as practice recognition and medical management of rare events. 28 The opportunity to practice in a safe learning environment with dedicated time for debriefing allows the development of competence that is not easily achieved in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Human patient simulation has been used for many years for teaching purposes [3][4][5][6][7][8] and was recently reported to be effective in training team response to trauma resuscitation. 9 Although simulation training is in its infancy in the medical field and is most commonly focused on individual skills such as endotracheal intubation, central venous catheter placement, and endoscopy training, its use is likely to increase. Settings that are especially prone to errors are those that are high acuity (risk) or low frequency, and those that require teamwork.…”
mentioning
confidence: 99%
“…Study results suggest that VR training has better skills transfer to the operative environment than video training. Both the VR-and videotrained participants improved; however, the VR-trained group improved more on the video trainer posttest than the This study 7 analyzed the use of a human patient simulator in trauma resuscitation training. Results showed that the trauma teams showed improvement in 4 of 5 scored and 6 of 8 timed tasks.…”
Section: Resultsmentioning
confidence: 99%